Kerajinan Gerabah di Desa Melikan Kecamatan Wedi Klaten Jawa Tengah - Irfan Hidayat (Jurnal Ilmu Sosial dan Humaniora, 2023)
Abstract This research aims to describe pottery crafts in Melikan village, Wedi sub-district, Klaten, Central Java, including the basic ideas for creating pottery, the materials and tools used, and the form of Wedi pottery crafts. This research uses a qualitative descriptive method, the instrument in this research is the researcher. To strengthen the research, researchers used observation, interview and documentation guidelines. The object of this research is the pottery craft industry in Wedi, Klaten, Central Java, and the research subjects are pottery craftsmen in Melikan village, Wedi subdistrict. The data analysis technique in this research is descriptive qualitative and uses stages, namely data collection, data reduction, data presentation, and drawing conclusions. Based on research results on pottery crafts in Wedi Klaten, Central Java, namely: The basic idea of creating pottery is motivated by market share or market orientation and also following the tastes of people who always demand maximum product production. The materials and tools used are Wedi clay as raw material for making pottery and munggur leaves as smoking material. The equipment used is mostly homemade, including a rotary table, gypsum mold, coconut leaf iron, cutting iron, scraper, tape measure, cutting wire, foam, boards and mosquito netting. The forms of pottery produced are eating and drinking utensils such as plates, bowls, teapots, piggy banks, then decorations such as flower vases, statues and jars.